Influence of biol with different preparations on the production of many (Harachis hypogaea L) - Moreira Saltos, Juan Ramón (2017)
The experiment was carried out at Agricultural Polytechnic of Manabí at El Limón campus, Calceta parish, Bolívar canton, Manabi province, Ecuador. The objective was to evaluate the effect of different biol preparations on peanut (Arachis hypogaea L.) productivity. Four formulations of biol were studied; Common biol (T1), Biol chelated (T2), Biol with lactic acid bacteria (T3) and Total biol. The biol was applied in drench at a concentration of 5% every 15 days up to 60 dds. A completely random design with four replicates was used. Productive variables were measured as: length (cm), pod number per plant and number of seeds per pod; root weight (g), biomass (kg. m2). The data were analyzed by analysis of variance and the means by Tukey to 0.05%. The results indicate that the biol type does not influence the productive variables. However, there are significant differences (p<0.05) in biomass where T1 and T4 exhibit the same behavior with 1.48 and 1.45 kg.m2. The results suggest that the biol type has its influence on the foliage without any relation to the production.